TENNESSEE - GOVT. - BOARDS - BOARD OF REGENTS - 1982: 1982 (1982)
Special Collections -- Banner Archives -- Clippings -- Drawer 4309

TENNESSEE - GOVT. - BOARDS - BOARD OF REGENTS - 1982-85-86-87-88-89: 1982-1989 (1982)
Special Collections -- Banner Archives -- Clippings -- Drawer 4309